2017
DOI: 10.1038/s41598-017-14940-6
|View full text |Cite
|
Sign up to set email alerts
|

How goats avoid ingesting noxious insects while feeding

Abstract: As mammalian herbivores feed, they often encounter noxious insects on plants. It is unknown how they handle such insects. We experimentally examined the behavioural responses of goats to the noxious spring-webworm (Ocnogyna loewii), and manipulated their sensory perception to reveal the process of insect detection. Goats did not avoid plants with webworms, demonstrating a remarkable ability to sort them apart from the plant (98% of webworms survived). Initial detection of webworms involved tactile stimulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…It is well known that mammalian herbivores have great impacts on the diversity, distribution, and fitness of plant communities and other herbivores, including insects [15,48]. Mammalian and insect herbivores often interact directly [49,50]. Here we demonstrate for the first time that…”
Section: Discussionmentioning
confidence: 53%
“…It is well known that mammalian herbivores have great impacts on the diversity, distribution, and fitness of plant communities and other herbivores, including insects [15,48]. Mammalian and insect herbivores often interact directly [49,50]. Here we demonstrate for the first time that…”
Section: Discussionmentioning
confidence: 53%
“…This ability to pick and choose forages results in relatively higher nutritional intake quality than would be predicted from analysis of the whole-plant diet ( Lu, 1988 ). Goats also possess an ability to “probe” and “shake” parts of individual plants, which can help them avoid noxious insects on individual leaves ( Berman et al, 2017 ). An ability to differentiate between and tolerate bitter flavors ( Bell, 1959 ) likely contributes to this diet flexibility.…”
Section: Natural Behavior Of Goatsmentioning
confidence: 99%
“…We performed dual and non-choice experiments as described by Berman et al . [13]. Briefly, we presented the kids with a choice between two bowls (in randomized order) containing leaves alone and leaves with webworms (henceforth ‘control leaves’ and ‘webworm leaves’, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies revealed that ungulates possess highly efficient behavioural mechanisms to avoid ingesting noxious IH while feeding [13,14]. Berman et al .…”
Section: Introductionmentioning
confidence: 99%